Adipocyte‐derived lipids modulate CD4+ T‐cell function. Issue 6 (24th April 2013) - Ioan‐Facsinay, Andreea; Kwekkeboom, Joanneke C.; Westhoff, Sanne; Giera, Martin; Rombouts, Yoann; van Harmelen, Vanessa; Huizinga, Tom W. J.; Deelder, André; Kloppenburg, Margreet; Toes, René E. M.
<x xml:space="preserve">Abstract</x> Adipose tissue contains several immune cells whose number and phenotype vary depending on the adiposity. In the present study, we show that IFN‐γ+ CD4+ T cells are enriched in human adipose tissue compared with in blood. To gain insight into the underlying mechanisms, we investigated the possibility that human adipocytes modulate CD4+ T‐cell cytokine production and proliferation and show that CD4+ T cells produced increased levels of IFN‐γ when activated in the presence of adipocytes. This effect was mediated by soluble mediators, as shown in transwell and adipocyte‐conditioned medium (ACM) transfer experiments. Additionally, ACM induced increased proliferation of CD4+ T cells upon activation. Intriguingly, the proliferation‐enhancing effect resided mainly in the lipid fraction of ACM, as shown upon separation of the protein and lipid fraction. Further separation of these lipids based on polarity revealed that the modulatory effect is confined to fractions containing free fatty acids. All identified fatty acids were able to individually enhance T‐cell proliferation. These data indicate that adipocytes can modulate CD4+ T‐cell function through the release of lipids. Remarkably, free fatty acids were the most prominent modulators of T‐cell proliferation, possibly leading to an accumulation of these cells in adipose tissue.